The effect of carbohydrate source and extrusion processing on growth performance on segregated early-weaned pigs - K Hongtrakul; J R Bergstrom; I H Kim; W B Nessmith Jr; Robert D Goodband; Keith C Behnke; Michael D Tokach; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1996)
A 21-day growth trial was conducted to determine the effect of various carbohydrate sources with or without moist extrusion processing on growth performance of segregated early-weaned pigs. Treatments included five different carbohydrate sources (corn, corn starch, rice, wheat flour, and grain sorghum) with or without moist extrusion processing in a 2 x 5 factorial arrangement. No interactions were observed among carbohydrate sources and extrusion processing. Growth performance was not improved by extrusion processing. Surprisingly, pigs fed corn had poorer growth performance compared to those fed other carbohydrate sources. These results suggest that corn starch, rice, wheat flour, and grain sorghum are suitable alternatives to corn in diets for segregated early-weaned pigs.; Swine Day, Manhattan, KS, November 21, 1996
Keywords: Swine day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 772; Swine; Segregated early-weaned pigs; Extrusion; Carbohydrate sources